Study of ectopic pregnancy in a tertiary care centre - Meena, Nitesh; Bairwa, Radheshyam; Sharma, Savitri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Ectopic pregnancy is an obstetric emergency with high morbidity and mortality. Incidence of ectopic pregnancies has been increasing in last two to three decades with reduction in mortality. The presenting symptoms include irregular vaginal bleeding. The present study was undertaken to study the clinical features of ectopic pregnancies in a tertiary care hospital. Methods: The present study on ectopic pregnancies was carried out in department of obstetrics and gynaecology, jhalawar medical college, Jhalawar, Rajasthan, India from January 2019 to October 2019. All patients admitted with diagnosis of ectopic pregnancy, either ruptured or unruptured where included in the study. Results: Total 52 patient of ectopic pregnancy were studies. Majority (63.46%) of patients belong to the age group 21-30 years. Ectopic pregnancy was most commonly noted in nulliparous woman (44.23%) Majority of the case (31%) had no risk factors among remaining (34.61%), previous MTP (17%), (17-30%) previous ectopic (9%) and PID (15-38%) were identified risk factors. Ampulla (75%) was the most common site for ectopic pregnancy. 57% of the cases were on the right side. The common presenting complaints were pain in abdomen (81%) bleeding/ spotting per vaginal (42%). There was no mortality. Conclusions: Surgical treatment was done more often because of patients reporting late to the hospital screening of high-risk case, early diagnosis and early intervention reduce the morbidity and mortality in ectopic pregnancies.